Africa Rising: Integrating Orange-fleshed Sweetpotato Scaling Out in Zambia - International Potato Center (2016)
We trained 214 decentralized vine multipliers in Lundazi, Chipata, Katete, and Petauke districts in preparation for the rainy season. These multipliers received 88,700 vine cuttings from the national research program (ZARI) screen house for further multiplication. Vines were distributed to 8,795 beneficiary households to expand root production.